Pyloric Dysfunction: A Review of the Mechanisms, Diagnosis, and Treatment - Hee Kyong Na; Andrew A. Li; Andres Gottfried-Blackmore; Alexander J. Podboy; Micaela M. Esquivel; Abel A. Joseph; Linda Nguyen; Joo Ha Hwang (Gut and Liver)
Pyloric dysfunction is defined as hypertonia or spasm of the pyloric sphincter. The pylorus plays a key role in gastric emptying, but its function remains incompletely understood. Most studies have focused on gastroparesis regardless of the underlying pathophysiology. Few studies have reported pyloric dysfunction in patients with gastroparesis, and the diagnostic and treatment modalities for pyloric dysfunction are not well established. Recently developed diagnostic modalities assessing pyloric function, such as high-resolution antroduodenal manometry and endoluminal functional lumen imaging, are currently being evaluated. A variety of therapeutic interventions targeting the pylorus, including pharmacologic agents, intrapyloric botulinum injection, endoscopic balloon dilation, stent insertion, surgical pyloroplasty, and gastric peroral endoscopic pyloromyotomy, have been proposed. Among these, gastric peroral endoscopic pyloromyotomy has emerged as a novel, minimally invasive therapy with demonstrated efficacy and safety for refractory gastroparesis. This article reviews the pathophysiology of pyloric dysfunction and the potential diagnostic and therapeutic modalities based on the latest literature.